Shifting paradigms in international investment law : more balanced, less isolated, increasingly diversified - Hindelang, Steffen; Krajewski, Markus, 1969- (Oxford : Oxford University Press, 2016)
In light of the controversies surrounding the impact of investment treaties and arbitration, this book reflects on the major changes in the area of international investment law.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 9, 2016).
Keywords: Investments, Foreign (International law); Law